Product Development Strategy Based on Local Wisdom to Strengthen the Identity of SMEs during Ramadan - Titin; Safa'atillah, Nurus; Sulaeman, Moh. Muklis; Cahyono, Puguh (PT. LITERASI SAINS NUSANTARA, 2024)
Ramadan is a crucial period for SMEs. During this month, consumer demand for Ramadan-specific products significantly increases. The objective of this research is to develop concrete strategies that can assist SMEs in leveraging local wisdom to produce products that reinforce their identity and enhance competitiveness in the market, particularly during Ramadan. This research method involves a literature review with a qualitative approach, focusing on descriptive analysis. Data for this study were extracted from scholarly articles published between 2001 and 2024, accessible through Google Scholar. The study findings indicate that product development strategies based on local wisdom to strengthen the identity of SMEs during Ramadan demonstrate significant value in supporting SME growth and preserving local cultural heritage. By harnessing the uniqueness of Ramadan culture and traditions, SMEs can create products that not only meet market needs but also reinforce local identity. A holistic approach involving deep understanding of cultural values, careful market analysis, cross-sector collaboration, and continuous evaluation are key to the success of this strategy.